Learning Innovation with Mobile Devices ICT In Majlis Ta’lim Raudhotun Nisa Jakarta, Indonesia - Nuraeni, Heni Ani (Nadwa, 2020)
Information Communication Technology (ICT) is a public demand in the industrial era 4.0. This study examines the use of mobile devices (ICT) in learning at the Majlis Ta’lim Raudhatun Nisa, Jakarta, Indonesia. Majlis ta'lim is a conventional Islamic educational institution for studying and practicing religious knowledge. The results of the study found that the majlis ta'lim Raudhotun Nisa was quickly responds to the demands of the times by making basic learning innovations. Learning does not only use conventional media but has used mobile devices in the form of projectors, laptops, and smartphones including WhatsApp, Facebook, and Instagram. Although most of the participants are elderly people who are not tech-savvy yet, the use of mobile devices has served as a means of socialization and communication and an effective means of modern learning. Abstrak: Teknologi Komunikasi Informasi (TIK) merupakan tuntutan masyarakat di era industri 4.0. Penelitian ini mengkaji pemanfaatan perangkat seluler (TIK) dalam pembelajaran di Majlis Ta'lim Raudhatun Nisa, Jakarta, Indonesia. Majlis ta'lim adalah lembaga pendidikan Islam konvensional untuk mempelajari dan mengamalkan ilmu agama. Hasil penelitian menemukan bahwa majelis ta'lim Raudhotun Nisa dengan cepat merespon tuntutan zaman dengan membuat inovasi pembelajaran dasar. Pembelajaran tidak hanya menggunakan media konvensional tetapi telah menggunakan perangkat mobile berupa proyektor, laptop, dan smartphone termasuk WhatsApp, Facebook, dan Instagram. Meski sebagian besar pesertanya adalah lansia yang belum paham teknologi, penggunaan perangkat seluler telah berfungsi sebagai sarana sosialisasi dan komunikasi serta sarana pembelajaran modern yang efektif.